A Qualitative Inquiry into Anatomy Teachers' Insights and Experiences with the use of Problem-based Questions in Medical Undergraduates Course of Bangladesh (Bangladesh Journal of Medical Education, 2026)
Background: Inclusion of problem-based questions in the teaching and assessment of medical undergraduates of Bangladesh is crucial for making a skilful physician in future. Teachers play an important role in teaching and assessment. Hence, it is very important to know the perceptions of teachers regarding the pivotal role of problem-based questions and their experiences. Objective: This study aimed to analyze the perceptions, views and experiences of Anatomy teachers of Bangladesh regarding problem-based questions. Methods: It was a cross-sectional descriptive study. Bangladesh Medical and Dental Council (BM&DC) registered postgraduate degree holders in Anatomy were selected as participants. Data were collected using a pretested self-administered questionnaire, and responses were scored using a five-point Likert scale. Results: The survey results on the perceptions, views and experiences of the Anatomy teachers of Bangladesh regarding problem-based questions were unified in four (4) out of five (5) sets of criteria that problem-based questions had influential role on undergraduates' “thought process”, “identifying undergraduates' strengths and weaknesses”, “improving skill and clinical reasoning ability”, and “intensification of exam preparation”. Here, the mean scores for the majority of the responses did not vary much. However, their opinions differed in “experience on constructing PBQs” with a varying range of mean scores from 2.81 ± 1.57 to 4.97 ± 0.18. Conclusion: Teachers of Bangladesh agreed that the incorporation of problem-based questions in regular discussion as well as in assessment will help the undergraduates to develop their clinical skills. Appropriate training of the teachers regarding problem-based questions is mandatory for improving the quality of teaching and assessment.BJME: Vol.-17, Issue-02, July, 2026: 37-48